2015
DOI: 10.5762/kais.2015.16.9.6180
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Smartphone Addiction among Elementary School Students

Abstract: The purpose of this study is to clarify the factors that affects smartphone addiction of elementary school students. The subjects were 263 students, from 4 elementary schools located in G-city. Data were collected from July, 2014 and analyzed using SPSS 19.0 program. The prevalence of addiction risk group and non-addicted group were 16.0% and 84.0%, respectively. The variables which had statistically significant differences with smart phone addiction of general characteristics are grade, living together family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Our findings on the direct relationship between media use time and media addiction are in line with previous studies on young [17] and late school-aged children (fifth and sixth grade of elementary school) [40]. In our data, 31.3% of the participants had a smartphone, and the average media use time per day amounted to 1.37 h. Based on a longitudinal study that examined the relationship between changes in media use time and media addiction among early school-aged children [16], children whose media use time continuously increased showed a strong tendency toward media addiction, as did those who spent more time using media at an early age.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on the direct relationship between media use time and media addiction are in line with previous studies on young [17] and late school-aged children (fifth and sixth grade of elementary school) [40]. In our data, 31.3% of the participants had a smartphone, and the average media use time per day amounted to 1.37 h. Based on a longitudinal study that examined the relationship between changes in media use time and media addiction among early school-aged children [16], children whose media use time continuously increased showed a strong tendency toward media addiction, as did those who spent more time using media at an early age.…”
Section: Discussionsupporting
confidence: 92%
“…The link between these dimensions and PSU is confirmed by their associations with the SAS subscales (Kwon, Lee, et al, 2013), which were particularly high especially between loss of control of smartphone use and nomophobia and the SAS subscales that measure tolerance and withdrawal. Moreover, personality traits that were previously identified as predictors of PSU, such as impulsivity, neuroticism, and low conscientiousness (Roberts et al, 2015; Ryu & Cho, 2015), were associated with these four SIS dimensions.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, a recent study showed that PSU is associated to posttraumatic stress disorder symptoms, in particular with two symptom clusters, namely negative alterations in cognitions and mood and physiological arousal symptoms (Contractor, Frankfurt, Weiss, & Elhai, 2017). Still from an addiction perspective, scholars have shown links between PSU and the personality traits typically associated with substance use, such as impulsivity (Roberts, Pullig, & Manolis, 2015; Ryu & Cho, 2015) and specific Big Five traits. In particular, Lane and Manner (2011) showed that more extraverted individuals were more likely to own a smartphone and to use it for texting, whereas more agreeable ones preferred calling than texting.…”
Section: Smartphone Overuse and Smartphone Addictionmentioning
confidence: 99%
“…Lee & Ogbolu, 2018;Lim & Kim, 2018;H. Park & Kim, 2016;Ryu & Cho, 2015;S.-G. Yoo et al, 2018). , 4 6 (S. Lee et al, 2016).…”
Section: -6mentioning
confidence: 99%